Positive electrode active material for lithium secondary battery, positive electrode for lithium secondary battery, lithium secondary battery, and method for producing positive electrode active material for lithium secondary battery

The development of a positive electrode active material for lithium secondary batteries, incorporating specific compositions and structural features, addresses the need for improved cycle characteristics, resulting in batteries with enhanced performance and longevity.

JP2025038616APending Publication Date: 2025-03-19SUMITOMO CHEM CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023145341
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-07
Publication Date
2025-03-19

AI Technical Summary

Technical Problem

There is a demand for lithium secondary batteries with improved cycle characteristics as their application fields expand.

Method used

A positive electrode active material for lithium secondary batteries is developed, comprising at least Li, Ba, and the element M (Ca or Al), with specific compositional ratios and structural features that include secondary particles with pores, where Ba is present in the pores and element M is on the surface, enhancing the battery's cycle performance.

Benefits of technology

The proposed solution enables lithium secondary batteries to achieve excellent cycle characteristics, with a cycle maintenance rate of 87% or more, thereby improving the battery's overall performance and longevity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025038616000002
    Figure 2025038616000002
  • Figure 2025038616000003
    Figure 2025038616000003
  • Figure 2025038616000004
    Figure 2025038616000004
Patent Text Reader

Abstract

To provide a positive electrode active material for a lithium secondary battery, which can provide a lithium secondary battery having excellent cycle characteristics.SOLUTION: A positive electrode active material for a lithium secondary battery includes at least Li, Ba, and an element M, the element M being one or more elements selected from the group consisting of Ca and Al, and satisfying the following (1) and (2). (1) (Q / X)×100<0.1. (2) 1≤(R / Y)×100. (X is the amount of Ba (unit: ppm) contained in a positive electrode active material for a lithium secondary battery measured by ICP emission spectroscopy, Y is the amount of element M (unit: ppm) contained in the positive electrode active material for the lithium secondary battery. Q is the amount of Ba (unit: ppm) contained in the filtrate obtained by measuring by ICP emission spectroscopy the filtrate obtained by filtering a suspension prepared by stirring the positive electrode active material for the lithium secondary battery and water in a mass ratio of 1:1, and R is the amount of element M (unit: ppm) contained in the filtrate.)SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a positive electrode active material for a lithium secondary battery, a positive electrode for a lithium secondary battery, a lithium secondary battery, and a method for producing a positive electrode active material for a lithium secondary battery. [Background technology]

[0002] For the positive electrode constituting the lithium secondary battery, a positive electrode active material for lithium secondary batteries is used.

[0003] For example, Patent Document 1 discloses a positive electrode active material for a non-aqueous electrolyte secondary battery, which includes a lithium transition metal composite oxide having secondary particles formed by aggregation of primary particles, and a surface modification layer on the surfaces of the primary particles. The surface modification layer included in the positive electrode active material for a non-aqueous electrolyte secondary battery disclosed in Patent Document 1 contains at least one of Sr and Ca, and Ba.

[0004] Patent Document 1 describes that the provision of the above-mentioned surface modification layer suppresses the reaction between the surface of the lithium transition metal composite oxide and the electrolyte and stabilizes the surface structure, thereby making it possible to suppress the decrease in battery capacity due to charge / discharge cycles. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] WO2021 / 152997A1 Summary of the Invention [Problem to be solved by the invention]

[0006] As the range of applications for lithium secondary batteries expands, there is a demand for improved cycle characteristics.

[0007] An object of the present invention is to obtain a positive electrode active material for a lithium secondary battery, which can provide a lithium secondary battery having excellent cycle characteristics.

[0008] A further object of the present invention is to provide a positive electrode for a lithium secondary battery containing the above-mentioned positive electrode active material for a lithium secondary battery, a lithium secondary battery, and a method for producing the positive electrode active material for a lithium secondary battery. [Means for solving the problem]

[0009] The present invention encompasses the following [1] to [9]. [1] A positive electrode active material for a lithium secondary battery, comprising at least Li, Ba, and an element M, the element M being one or more elements selected from the group consisting of Ca and Al, and satisfying the following (1) and (2): (1) (Q / X) × 100 < 0.1 (2) 1≦(R / Y)×100 (In (1) and (2), X is the amount of Ba (unit: ppm) contained in the positive electrode active material for lithium secondary batteries, as measured by ICP emission spectroscopy; Y is the amount of element M (unit: ppm) contained in the positive electrode active material for lithium secondary batteries; Q is the amount of Ba (unit: ppm) contained in the filtrate, as measured by ICP emission spectroscopy, obtained by filtering a suspension prepared by stirring the positive electrode active material for lithium secondary batteries and water in a mass ratio of 1:1; and R is the amount of element M (unit: ppm) contained in the filtrate.) [2] The positive electrode active material for a lithium secondary battery according to [1], wherein the filtrate has a pH of 12 or less when the liquid temperature is 25° C. [3] BET specific surface area is 2.0m 2 / g or less. [4] The positive electrode active material for a lithium secondary battery according to any one of [1] to [3], which satisfies the following formula (I): Li:Ni:M1:Ba:M2=a:(1-bcd):b:c:d...Formula (I) (M1 is one or more elements selected from the group consisting of Co and Mn, M2 is one or more elements selected from the group consisting of Al, Ca, Fe, Cu, Ti, Mg, Zn, Sn, Zr, Ga, W, Mo, Nb, B, Si, S, and P, and the formula (I) satisfies 0.9 ≦ a ≦ 1.2, 0 ≦ b ≦ 0.2, 0 < c ≦ 0.03, and 0 < d ≦ 0.2.) [5] The positive electrode active material for a lithium secondary battery contains secondary particles that are aggregates of primary particles, the secondary particles have pores, and in a cross-sectional image of the secondary particles at a magnification of 5000 obtained by a scanning electron microscope, Ba is present in the pores. The positive electrode active material for a lithium secondary battery according to any one of [1] to [4]. [6] After fully charging a lithium secondary battery manufactured using the positive electrode active material for a lithium secondary battery at 4.3 V, the maximum value of the oxygen release rate obtained by performing differential thermal - thermogravimetric simultaneous analysis on the positive electrode active material layer contained in the lithium secondary battery after charging is 1.5% / min or less. The positive electrode active material for a lithium secondary battery according to any one of [1] to [5]. [7] A positive electrode for a lithium secondary battery containing the positive electrode active material for a lithium secondary battery according to any one of [1] to [6]. [8] A lithium secondary battery having the positive electrode for a lithium secondary battery according to [7]. [9] A manufacturing method of a positive electrode active material for a lithium secondary battery, including a mixing step of mixing a metal composite compound, a lithium compound, and a compound containing Ba to obtain a mixture, a firing step of firing the mixture to obtain a fired product, and an adding step of adding a compound containing element M to the fired product, wherein the element M is one or more elements selected from the group consisting of Ca and Al.

Advantages of the Invention

[0010] According to the present invention, a positive electrode active material for a lithium secondary battery capable of providing a lithium secondary battery with excellent cycle characteristics can be obtained. Furthermore, a positive electrode for a lithium secondary battery, a lithium secondary battery, and a manufacturing method of a positive electrode active material for a lithium secondary battery containing such a positive electrode active material for a lithium secondary battery can be provided.

Brief Description of the Drawings

[0011] [Figure 1] FIG. 1 is a schematic diagram illustrating an example of a lithium secondary battery. [Diagram 2] FIG. 1 is a schematic diagram showing the overall configuration of an all-solid-state lithium secondary battery. [Diagram 3] 1 is an SEM image of a cross section of the positive electrode active material for a lithium secondary battery of Example 1. [Figure 4] 1 is a SEM-EDX image of a cross section of the positive electrode active material for a lithium secondary battery of Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] In this specification, metal composite compound is hereinafter referred to as "MCC" and cathode active material for lithium secondary batteries is hereinafter referred to as "CAM." Lithium secondary batteries refer to lithium ion batteries.

[0013] "Ni" refers to nickel atoms, not nickel metal. Similarly, "Co" and "Li" refer to cobalt atoms, lithium atoms, etc.

[0014] For example, when a numerical range is described as "1-10 μm" or "1 to 10 μm," it means a range from 1 μm to 10 μm, including the lower limit of 1 μm and the upper limit of 10 μm.

[0015] [Method of measuring cycle maintenance rate] In this specification, the term "excellent cycle characteristics" means that the cycle retention rate measured using a lithium secondary battery prepared by the method described below is 87% or more.

[0016] <Preparation of lithium secondary battery> [Preparation of positive electrodes for lithium secondary batteries] A paste-like positive electrode mixture is prepared by adding and kneading CAM, a conductive material (acetylene black), and a binder (PVdF) in a ratio of CAM:conductive material:binder = 92:5:3 (mass ratio). When preparing the positive electrode mixture, N-methyl-2-pyrrolidone is used as an organic solvent.

[0017] The obtained positive electrode mixture is applied to a 20 μm thick Al foil as a current collector and vacuum dried at 150 °C for 8 hours to obtain a positive electrode for a lithium secondary battery. The electrode area of ​​this positive electrode for a lithium secondary battery is 1.65 cm 2 Let us assume that.

[0018] [Preparation of lithium secondary batteries] The following operations are carried out in a glove box under an argon atmosphere. The above-mentioned positive electrode for lithium secondary battery is placed on the bottom cover of a part for coin-type battery R2032 (manufactured by Hosen Co., Ltd.) with the aluminum foil side facing down, and a 25 μm thick separator (polyethylene porous film) is placed on top of it. 300 μl of electrolyte is poured here. The electrolyte is a liquid in which LiPF6 is dissolved at a ratio of 1 mol / l in a mixture of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate in a volume ratio of 30:35:35. Next, metallic lithium is used as the negative electrode, placed on the top of the separator, and the top lid is placed over the gasket and crimped with a crimping machine to produce a lithium secondary battery (coin-type half cell R2032).

[0019] The assembled lithium secondary battery is allowed to stand at room temperature for 12 hours to allow the separator and the positive electrode mixture layer to be sufficiently impregnated with the electrolyte. At a test temperature of 25°C, the charging and discharging currents are set to 0.2 CA, and constant current and constant voltage charging and constant current discharging are performed, respectively. The maximum charging voltage is 4.3 V, and the minimum discharging voltage is 2.5 V. Next, constant current / constant voltage charging and constant current discharging were repeated under the following conditions at a test temperature of 25° C. The charge / discharge cycle was repeated 50 times. Charging: Current setting value 1CA, maximum voltage 4.3V, constant voltage constant current charging Discharge: Battery setting value 1CA, minimum voltage 2.5V, constant current discharge The cycle retention rate was calculated from the discharge capacity at the 1st cycle and the discharge capacity at the 50th cycle using the following formula. A higher cycle retention rate indicates better cycle characteristics. Cycle retention rate (%) = 50th cycle discharge capacity (mAh / g) / 1st cycle discharge capacity (mAh / g) × 100 (formula)

[0020] [Composition analysis] The composition of CAM can be measured by dissolving the CAM in an acid or alkali depending on the element to be measured, and then using an ICP optical emission spectrometer, such as Optima 7300 (manufactured by PerkinElmer Co., Ltd.).

[0021] [BET specific surface area] The BET specific surface area is a value measured by the BET (Brunauer, Emmett, Teller) method. BET specific surface area (unit: m 2 For example, 1 g of CAM powder is dried in a nitrogen atmosphere at 105° C. for 30 minutes, and then the specific surface area can be measured using a BET specific surface area meter (for example, Macsorb (registered trademark) manufactured by Mountec Co., Ltd.).

[0022] <Positive electrode active material for lithium secondary batteries> The CAM of this embodiment preferably contains secondary particles that are aggregates of primary particles. CAM is particulate. In this specification, the term "primary particle" refers to a particle that does not have grain boundaries on its surface. More specifically, the term "primary particle" refers to a particle that does not have clear grain boundaries on its surface when observed at a magnification of 5000-20000 times using a scanning electron microscope or the like. The term "secondary particle" refers to a particle in which a plurality of the primary particles are three-dimensionally bonded with gaps between them. The secondary particle has a spherical or nearly spherical shape. For example, the secondary particle is formed by agglomeration of 10 or more primary particles.

[0023] The secondary particles preferably have pores. Pores are gaps formed between aggregated primary particles. The pores may be closed pores surrounded by primary particles, or open pores communicating with the surfaces of secondary particles.

[0024] CAM contains at least Li, Ba, and an element M. The element M is one or more elements selected from the group consisting of Ca and Al. The CAM preferably contains secondary particles, and has Ba in the pores of the secondary particles and element M at least on the surface of the secondary particles. In this specification, the surface of the CAM or secondary particles refers to the portion that comes into contact with water when preparing a suspension, which will be described later. The interior of the CAM or secondary particles refers to the portion closer to the center of the particle than the surface of the CAM or secondary particles. The interior of the CAM or secondary particles is less likely to come into contact with water than the surface of the CAM or secondary particles.

[0025] CAM satisfies the following (1) and (2). (1) (Q / X) × 100 < 0.1 (2) 1≦(R / Y)×100 (In (1) and (2), X is the amount of Ba (unit: ppm) contained in the CAM measured by ICP emission spectroscopy, Y is the amount of element M (unit: ppm) contained in the CAM, Q is the amount of Ba (unit: ppm) contained in the filtrate obtained by filtering a suspension prepared by stirring the CAM and water in a mass ratio of 1:1, and measuring the filtrate by ICP emission spectroscopy, and R is the amount of element M (unit: ppm) contained in the filtrate.)

[0026] [Measuring method for X and Y] X and Y are measured by the method described in the above [Composition Analysis]. X and Y indicate the proportions of the elements contained in the CAM relative to the total amount (100 mass%) of the elements detected by an ICP spectroscopic analyzer.

[0027] [Method of measuring Q and R] The filtrate is obtained by filtering a suspension prepared by stirring CAM and water in a mass ratio of 1: 1. As the water, for example, ion-exchanged water or pure water can be used. At this time, the liquid temperature of the water is adjusted to 20° C., and the mixture is stirred at a stirring speed of 500 rpm for 20 minutes to prepare a suspension. The resulting suspension is filtered to obtain a filtrate. The filtration is performed once. Q and R are obtained by measuring the filtrate using an ICP emission spectrometer. Q is the amount of Ba dissolved from CAM into water, and R is the amount of element M dissolved. Q and R indicate the proportions of the elements contained in the filtrate relative to the total amount (100 mass%) of the elements detected by the ICP spectroscopic analyzer.

[0028] In measuring Q and R, since the effect of particle size on the amount of elution is slight, the particle size of the sample used in the measurement is not particularly limited.

[0029] The pH of the obtained filtrate at a liquid temperature of 25°C is preferably 12 or less, and more preferably less than 12. CAM with a filtrate having a pH of 12 or less or less than 12 has a small amount of Li remaining on the surface, which makes it easy to improve cycle characteristics and to prevent gelation during electrode preparation. The lower limit of the pH is not particularly limited, but may be 1.0 or more. The pH is preferably 1.0 to 12, and more preferably 1.0 or more and less than 12.

[0030] A CAM that satisfies the above (1) means that the amount of Ba dissolved out of the Ba contained in the CAM is small. A small amount of Ba dissolved out means that Ba is present in the CAM more intensively in the interior than on the surface of the CAM. In this case, Ba may exist as a Ba compound. The Ba compound is a compound containing at least Ba, such as BaCO3, BaSO4, and BaO.

[0031] A CAM that satisfies the above (2) means that, among the element M contained in the CAM, a large amount of element M is dissolved. A large amount of element M dissolved means that element M is present at least on the surface of the CAM. Element M may be present both on the surface and inside of the CAM. Element M may exist as an element M compound. The element M compound is a compound having at least the element M, such as CaO, Ca(OH)2, CaSO4, CaCO3, Al2O3, Al(OH)3, Al2(SO4)3, and Al2(CO3)3.

[0032] In the CAM that satisfies the above (1) and (2), Ba is present inside the CAM, and the element M is present at least on the surface of the CAM. The inventors have found that the use of such a CAM improves the cycle characteristics of a lithium secondary battery. The reason for this is presumed to be as follows.

[0033] The lithium compounds used in the manufacture of CAM may remain unreacted in the CAM and may react with carbon dioxide in the air to produce lithium carbonate. LiPF6 is widely used as a solute in the electrolyte of lithium secondary batteries. LiPF6 reacts with water during charging to generate hydrofluoric acid. When this hydrofluoric acid reacts with the lithium carbonate in CAM, carbon dioxide, or gas, is generated. When CAM is pressed during the production of lithium secondary batteries, or when it is repeatedly charged and discharged as a secondary battery, the particles can crack, creating new surfaces inside the secondary particles. If lithium carbonate is present on the newly created surface, the above reaction generates gas. In the CAM that satisfies the above (1), Ba exists inside the CAM, so when a new surface is generated, Ba reacts with hydrofluoric acid. As a result, the reaction between lithium carbonate and hydrofluoric acid is suppressed. Therefore, gas is not easily generated even when charging and discharging are repeated, and the cycle characteristics are not easily deteriorated.

[0034] In addition, when the CAM comes into direct contact with the electrolyte and a voltage is applied, side reactions that do not contribute to the charge and discharge reactions occur, and the cycle characteristics tend to deteriorate. Side reactions include oxidative decomposition of the electrolyte. In the CAM satisfying the above (2), the secondary particles are covered and protected by the element M compound. In this case, the secondary particles are unlikely to come into direct contact with the electrolyte, and the electrolyte is unlikely to be oxidized and decomposed. Therefore, even if charging and discharging are repeated, side reactions are unlikely to occur, and the cycle characteristics are unlikely to deteriorate. In addition, since the surface of the secondary particles is covered with the element M compound, the reaction between lithium carbonate and hydrofluoric acid on the surface of the secondary particles is suppressed, and gas is unlikely to be generated.

[0035] "(Q / X)×100" is more than 0, preferably 0.001 or more, more preferably 0.005 or more, and even more preferably 0.01 or more. When "(Q / X)×100" is more than 0, preferably equal to or greater than the lower limit, Ba is appropriately present in the CAM, so that the cycle characteristics are less likely to deteriorate. "(Q / X)×100" is preferably 0.09 or less, more preferably 0.08 or less, and even more preferably 0.06 or less. When "(Q / X)×100" is equal to or less than the upper limit, the reaction between lithium carbonate and hydrofluoric acid can be further suppressed, so that the cycle characteristics are less likely to deteriorate. With respect to (Q / X)×100, the following (1)-1 is preferable, (1)-2 is more preferable, (1)-3 is further more preferable, and (1)-4 is particularly preferable. (1)-1 0.001≦(Q / X)×100<0.1 (1)-2 0.005≦(Q / X)×100≦0.09 (1)-3 0.01≦(Q / X)×100≦0.08 (1)-4 0.01≦(Q / X)×100≦0.06

[0036] "(R / Y)×100" is preferably 20 or less, more preferably 15 or less, and even more preferably 10 or less. When (R / Y)×100 is the upper limit or less, in the CAM, the element M compound is present at least on the surface of the secondary particles, and a part of the secondary particles is exposed, so that the insertion reaction and desorption reaction of lithium ions are concentrated in the exposed part of the secondary particles, and the ionic conductivity is easily improved. As a result, the cycle characteristics can be improved. (R / Y)×100 is preferably 1.5 or more, and more preferably 2.0 or more. When (R / Y)×100 is the lower limit or more, the element M compound is moderately coated, and the oxidative decomposition of the electrolyte is less likely to occur, so that the cycle characteristics are less likely to decrease.

[0037] The above (2) is preferably the following (2)-1, more preferably (2)-2, and further preferably (2)-3. (2)-1 1≦(R / Y)×100≦20 (2)-2 1.5≦(R / Y)×100≦15 (2)-3 2.0≦(R / Y)×100≦10

[0038] X is preferably 2000 ppm or more, more preferably 2500 ppm or more. Also, X is preferably 10000 ppm or less, more preferably 9500 ppm or less. When X is in the above range, it means that Ba, which contributes to improving cycle characteristics, is sufficiently contained in the CAM. X is preferably 2000 to 10000 ppm, more preferably 2500 to 9500 ppm.

[0039] Y is preferably 13000 ppm or more, more preferably 15000 ppm or more. Also, Y is preferably 30000 ppm or less, more preferably 28000 ppm or less. When Y is in the above range, it means that the element M that contributes to improving cycle characteristics is sufficiently present in the CAM. Y is preferably 13,000 to 30,000 ppm, more preferably 15,000 to 28,000 ppm.

[0040] Q is preferably 0.01 ppm or more, more preferably 0.05 ppm or more. Also, Q is preferably 10 ppm or less, more preferably 5 ppm or less. When Q is in the above range, the amount of Ba present on the surface of the CAM is small, and compounds that may become resistance are unlikely to exist on the surface, so that the cycle characteristics can be improved. Q is preferably 0.01 to 10 ppm, more preferably 0.05 to 5 ppm.

[0041] R is preferably 300 ppm or more, more preferably 400 ppm or more. R is preferably 3000 ppm or less, more preferably 2500 ppm or less. When R is within the above range, an appropriate amount of element M compound is present on the surface of the CAM, and oxidative decomposition of the electrolyte solution is less likely to occur, thereby improving cycle characteristics. R is preferably 300 to 3000 ppm, more preferably 400 to 2500 ppm.

[0042] The BET specific surface area of ​​CAM is 2.0m 2 / g or less, and 1.95m 2 / g or less is more preferable, and 1.90m 2 The BET specific surface area of ​​CAM is preferably 0.1 m 2 / g or more, and 0.15m 2 / g or more is more preferable, and 0.20m 2 It is more preferable that the molecular weight is 1 / g or more.

[0043] BET specific surface area is 0.1-2.0m 2 / g, preferably 0.15-1.95m 2 / g, more preferably 0.20-1.90m 2 It is more preferable that the molecular weight is / g.

[0044] When using a CAM with a BET specific surface area equal to or greater than the above lower limit value, it is easy to improve the output characteristics of the lithium secondary battery. When using a CAM with a BET specific surface area equal to or less than the above upper limit value, it is difficult for the contact area between the CAM and the electrolyte to increase, and it is less likely for gas generated due to the decomposition of the electrolyte to occur. As a result, the cycle characteristics are less likely to deteriorate.

[0045] The CAM preferably satisfies the following formula (I). Li:Ni:M1:Ba:M2=a:(1-b-c-d):b:c:d ··· Formula (I) (M1 is one or more elements selected from the group consisting of Co and Mn, M2 is one or more elements selected from the group consisting of Al, Ca, Fe, Cu, Ti, Mg, Zn, Sn, Zr, Ga, W, Mo, Nb, B, Si, S, and P, and formula (I) satisfies 0.9≦a≦1.2, 0≦b≦0.2, 0<c≦0.03, and 0<d≦0.2.)

[0046] ·a a is preferably 0.95 or more, more preferably 1.00 or more. Also, a is preferably 1.15 or less, more preferably 1.10 or less. Formula (I) preferably satisfies 0.95≦a≦1.15, more preferably 1.00≦a≦1.10.

[0047] ·b + c + d From the perspective of improving the cycle characteristics, b + c + d is preferably 0.25 or less, more preferably 0.20 or less. Also, b + c + d is preferably 0.06 or more, more preferably 0.07 or more. Formula (I) preferably satisfies 0.06≦b + c + d≦0.25, more preferably 0.07≦b + c + d≦0.20.

[0048] ·b b is preferably 0.001 or more, more preferably 0.005 or more. Also, b is preferably 0.18 or less, more preferably 0.15 or less. Formula (I) preferably satisfies 0.001≦b≦0.18, more preferably 0.005≦b≦0.15.

[0049] ·c From the viewpoint of improving cycle characteristics, c is preferably 0.001 or more, and more preferably 0.005 or more, and is preferably 0.025 or less, and more preferably 0.020 or less. Formula (I) preferably satisfies 0.001≦c≦0.025, and more preferably satisfies 0.005≦c≦0.020.

[0050] d From the viewpoint of improving cycle characteristics, d is preferably 0.001 or more, more preferably 0.005 or more, and is preferably 0.1 or less. Formula (I) preferably satisfies 0.001≦d≦0.2, and more preferably satisfies 0.005≦d≦0.1.

[0051] From the viewpoint of obtaining a lithium secondary battery having excellent cycle characteristics, M2 is preferably one or more elements selected from the group consisting of Al, Ca, Ti, Mg, Zn, Sn, Zr, W, Mo, Nb, B, Si, S and P, and more preferably one or more elements selected from the group consisting of Al, Ca, Ti, Mg, Zr, W, Nb and B.

[0052] In the CAM, Ba is preferably present in the pores of the secondary particles in a cross-sectional image of the secondary particles at a magnification of 5000 times obtained by a scanning electron microscope (SEM). When Ba is present in the pores of the secondary particles, hydrofluoric acid reacts with Ba efficiently, and the reaction between lithium carbonate and hydrofluoric acid is further suppressed. Therefore, the cycle characteristics are less likely to deteriorate.

[0053] [How to check Ba on secondary particle cross section] An example of a method for obtaining a cross section of a secondary particle of CAM is to process the secondary particle with an ion milling device. Specifically, the cross section can be obtained by the following method. First, CAM is dispersed in a resin for fixing particles. After that, the mixture is vacuum degassed, and the resulting product is sandwiched between aluminum plates and cured. This results in a cured resin containing CAM. The cured product is fixed to a sample stage and set in a cross section sample preparation device (also called a cross section polisher, for example, IB-19520CCP, manufactured by JEOL). The cross section of the secondary particle of CAM is prepared by argon ion beam processing at an ion acceleration voltage of 6.0 kV. In order to obtain a cross-section of a secondary particle of CAM contained in a positive electrode, a part of a positive electrode made using CAM may be cut out and processed with an ion milling device to obtain a cross-section of a secondary particle of CAM contained in a positive electrode active material layer.

[0054] The cross section of the secondary particles obtained by the above processing is observed by a backscattered electron image using a SEM to obtain a cross section image of the secondary particles. The measurement conditions can be, for example, an acceleration voltage of 5 kV, image resolution of x and y = 0.023 μm, z = 0.023 μm, and a magnification of 5000 times.

[0055] FIG. 3 is an SEM image of the cross section of the CAM. FIG. 4 is an SEM-EDX image of Ba mapping of the cross section of the CAM. Note that the SEM image is an image obtained by a scanning electron microscope, SEM-EDX is scanning electron microscope-energy dispersive X-ray spectroscopy, and the SEM-EDX image is an image obtained by measurement using SEM-EDX. As an SEM-EDX device, a Schottky field emission scanning electron microscope (manufactured by JEOL Ltd., product name JSM-7900F) equipped with Oxford Instruments' X-Max 150 as an EDX detector can be used. In Fig. 4, the area where Ba is mapped on the cross section of the CAM is shown in gray. The lighter gray area in the upper right of Fig. 4 is an area where Ba compounds that did not enter the pores have aggregated.

[0056] Comparing Figure 3 and Figure 4, the area where Ba is mapped in Figure 4 overlaps with the area where the white areas are observed in Figure 3. From these results, it can be seen that the white areas in Figure 3 are Ba. Furthermore, the white areas are also the positions of the pores of the secondary particles, and Figure 3 shows that Ba is located in the pores present inside the CAM.

[0057] It is preferable that the maximum oxygen release rate obtained by simultaneous differential thermal and thermogravimetric analysis of the positive electrode active material layer contained in the lithium secondary battery after the charging, after the lithium secondary battery prepared using the CAM is fully charged at 4.3 V, is 1.5% / min or less. Fully charging means charging until the charging rate of the lithium secondary battery reaches 100%.

[0058] [Method for measuring oxygen release rate] The oxygen release rate can be measured, for example, by the following method.

[0059] First, a lithium secondary battery containing the CAM to be measured is manufactured by the method described in the above <Lithium secondary battery>. This lithium secondary battery is fully charged by constant current and constant voltage charging under the conditions of a test temperature of 25°C, a maximum charging voltage of 4.3V, and a charging current of 0.1CA. Thereafter, in a glove box in an argon gas atmosphere, the positive electrode taken out of the lithium secondary battery after the full charge is washed with dimethyl carbonate to remove the electrolyte adhering to the positive electrode. Then, the washed positive electrode is dried to remove the cleaning solution adhering to the positive electrode. Then, the positive electrode active material layer applied on the Al foil of the positive electrode is scraped off using ceramic tweezers to obtain a sample. The sample is then analyzed by the following (method of simultaneous differential thermal-thermogravimetric analysis).

[0060] (Method of simultaneous differential thermal and thermogravimetric analysis) As a measuring device for simultaneous differential thermal analysis and thermogravimetry, STA7300 manufactured by Hitachi High-Tech Science Corporation can be used. The samples are weighed on the balance beam of the STA7300. Approximately 10 mg of sample is weighed out, placed in an aluminum measuring container, and set in the above-mentioned measuring device. The temperature is raised from 20 to 400°C at a rate of 5°C / min under a nitrogen flow of 5 ml / min to obtain a DTA curve. The oxygen release rate is determined from the weight change in the obtained DTA curve.

[0061] When heat is applied to the positive electrode active material layer after full charging, oxygen is likely to be released due to thermal decomposition of CAM in the positive electrode active material layer. However, in CAM with a maximum oxygen release rate of 1.5% / min or less, the crystal structure of CAM is likely to be stable, and cycle characteristics are unlikely to deteriorate. The maximum oxygen release rate is 0% / min or more, or exceeds 0% / min. The maximum oxygen release rate is preferably 0 to 1.5% / min or less, and more preferably exceeds 0% / min and is 1.5% / min or less.

[0062] The CAM preferably has a layered structure, and more preferably has a hexagonal crystal structure or a monoclinic crystal structure.

[0063] The hexagonal crystal structure is P3, P31, P32, R3, P-3, R-3, P312, P321, P3112, P3121, P3212, P3221, R32, P3m1, P 31m, P3c1, P31c, R3m, R3c, P-31m, P-31c, P-3m1, P-3c1, R-3m, R-3c, P6, P61, P65, P62, P64, P63 , P-6, P6 / m, P63 / m, P622, P6122, P6522, P6222, P6422, P6322, P6mm, P6cc, P63cm, P63mc, P-6m2, P-6c2, P-62m, P-62c, P6 / mmm, P6 / mcc, P63 / mcm, and P63 / mmc.

[0064] In addition, the monoclinic crystal structure belongs to any one space group selected from the group consisting of P2, P21, C2, Pm, Pc, Cm, Cc, P2 / m, P21 / m, C2 / m, P2 / c, P21 / c, and C2 / c.

[0065] From the perspective of obtaining a lithium secondary battery with excellent cycle characteristics, it is more preferable that CAM has a hexagonal crystal structure belonging to the space group R-3m or a monoclinic crystal structure belonging to C2 / m.

[0066] [Method for confirming crystal structure] The crystal structure of CAM can be confirmed by observing it using a powder X-ray diffractometer (for example, UltimaIV manufactured by Rigaku Corporation).

[0067] [Manufacturing method of CAM] The manufacturing method of CAM includes a mixing step of mixing MCC, a lithium compound, and a compound containing Ba to obtain a mixture, a firing step of firing the mixture to obtain a fired product, and an addition step of adding a compound containing element M to the fired product. These will be described in order below.

[0068] [Mixing step] First, prepare MCC containing at least Ni. MCC can be manufactured by the batch coprecipitation method or the continuous coprecipitation method. Hereinafter, taking a metal composite oxide containing Ni, Mn, and Al as an example, its manufacturing method will be described in detail.

[0069] First, by the coprecipitation method, particularly the continuous coprecipitation method described in JP-A-2002-201028, as an example, a nickel salt solution, a manganese salt solution, an aluminum salt solution, and a complexing agent are reacted to produce a metal composite hydroxide represented by Ni (1-b-d) Mn b Al d (OH)2 (where b and d are the same as in the above formula (I)).

[0070] As the nickel salt that is the solute of the nickel salt solution, for example, one or more of nickel sulfate, nickel nitrate, nickel chloride, and nickel acetate can be used.

[0071] As the manganese salt that is the solute of the manganese salt solution, for example, one or more of manganese sulfate, manganese nitrate, manganese chloride, and manganese acetate can be used.

[0072] As the aluminum salt which is the solute of the aluminum salt solution, for example, aluminum sulfate, sodium aluminate, etc. can be used.

[0073] The above metal salts are (1-b-d) Mn b Al d It is used in a ratio corresponding to the composition ratio of (OH)2. Water is also used as the solvent.

[0074] The complexing agent is a compound capable of forming a complex with Ni, Mn, and Al ions in an aqueous solution, such as ammonium ion donors, hydrazine, ethylenediaminetetraacetic acid, nitrilotriacetic acid, uracildiacetic acid, and glycine.

[0075] Examples of the ammonium ion donor include ammonium salts such as ammonium hydroxide, ammonium sulfate, ammonium chloride, ammonium carbonate, and ammonium fluoride.

[0076] When a complexing agent is used, the amount of the complexing agent contained in the mixed liquid containing the nickel salt solution, the manganese salt solution, the aluminum salt solution, and the complexing agent is, for example, a molar ratio of more than 0 and not more than 2 to the total number of moles of the metal salts contained in the mixed liquid.

[0077] In the coprecipitation method, in order to adjust the pH value of the mixture, an alkaline aqueous solution is added to the mixture before the pH of the mixture becomes neutral from alkaline. The alkaline aqueous solution can be an aqueous solution of sodium hydroxide or potassium hydroxide.

[0078] In this specification, the pH value is defined as the value measured when the temperature of the mixed liquid is 40° C. If the temperature of the mixed liquid sampled from the reaction tank is not 40° C., the mixed liquid is heated or cooled to 40° C. before measuring the pH.

[0079] During the reaction, the temperature of the reaction vessel is controlled within the range of, for example, 20 to 80°C, preferably 30 to 70°C.

[0080] During the reaction, the pH value in the reaction tank is controlled within the range of, for example, 9 to 13, and preferably 10 to 13.

[0081] The materials in the reaction vessel are mixed by suitable stirring. As a reaction vessel used in the continuous coprecipitation method, an overflow type reaction vessel can be used in order to separate the formed reaction precipitate.

[0082] In order to control the inside of the reaction vessel to a desired atmosphere, a specific gas may be passed through the reaction vessel or the reaction liquid may be directly bubbled into the reaction vessel.

[0083] After the above reaction, the resulting reaction precipitate is washed with water, dehydrated by centrifugation, suction filtration, etc., and dried to obtain a metal composite hydroxide. If necessary, the reaction precipitate may be washed with weak acid water or an alkaline solution containing sodium hydroxide or potassium hydroxide.

[0084] When a metal composite oxide is produced as MCC, the resulting metal composite hydroxide is oxidized to obtain the metal composite oxide.

[0085] The oxidation time, which is the total time from the start of temperature increase to the end of temperature maintenance after the temperature has been reached, is preferably 2 to 10 hours. The oxidation temperature is preferably 500 to 800°C.

[0086] During the oxidation, various gases, for example, inert gases such as nitrogen, argon, and carbon dioxide, air, oxidizing gases such as oxygen, and mixtures thereof may be supplied into the reaction vessel.

[0087] After drying, the MCC may be classified as appropriate.

[0088] MCC, a lithium compound, and a compound containing Ba are mixed to obtain a mixture. The lithium compound may be at least one of lithium carbonate, lithium nitrate, lithium acetate, lithium hydroxide, lithium hydroxide hydrate, lithium oxide, lithium chloride, and lithium fluoride. Of these, any one of lithium hydroxide, lithium hydroxide hydrate, and lithium carbonate or a mixture thereof is preferred.

[0089] Examples of compounds containing Ba include barium hydroxide, barium nitrate, and barium carbonate.

[0090] The compound containing Ba is added in an amount such that Ba is preferably more than 0 mol% and 3 mol% or less, more preferably 0.01-2.5 mol%, and even more preferably 0.05-2.0 mol% relative to the total amount of elements other than oxygen (e.g., Ni, M1, M2) contained in MCC. By setting the amount of the Ba-containing compound to the above range, it is possible to produce CAM that satisfies the above (1) and preferably has an oxygen release rate within the above range. By adding the Ba-containing compound in the mixing step, crystal growth is promoted during firing, and the pores of the secondary particles of the obtained CAM are sufficiently formed, which tends to increase the BET specific surface area. As a result, the cycle characteristics of the lithium secondary battery can be improved.

[0091] The Ba-containing compound, the lithium compound, and MCC are mixed in consideration of the composition ratio of the final target product to obtain a mixture of the Ba-containing compound, the lithium compound, and MCC. The amount (molar ratio) of Li contained in the lithium compound relative to the total amount of elements other than oxygen (e.g., Ni, M1, M2) contained in MCC is preferably 0.9 to 1.10, more preferably 0.91 to 1.09, and even more preferably 0.92 to 1.08.

[0092] [Firing process] The mixture is fired to obtain a fired product. By firing the mixture, crystal growth is promoted, the pores are increased, the BET specific surface area is increased, and CAM having Ba present in the pores can be produced. For firing, dry air, an oxygen atmosphere, or the like is used depending on the desired composition. In this embodiment, firing in an oxygen atmosphere is preferred.

[0093] The firing process may involve only one firing step, or may involve multiple firing steps. When multiple firing steps are performed, the step in which the firing is performed at the highest temperature is referred to as the main firing. Prior to the main firing, a preliminary firing at a temperature lower than the main firing may be performed. In addition, after the main firing, a post-firing at a temperature lower than the main firing may be performed.

[0094] In the firing step, it is preferable to first perform pre-firing and then main firing.

[0095] The calcination temperature during the calcination is preferably 600 to 900° C., more preferably 610 to 850° C., and even more preferably 620° C. or higher and lower than 700° C. When the calcination temperature is equal to or higher than the lower limit, a CAM having a strong crystal structure can be obtained. On the other hand, when the calcination temperature is equal to or lower than the upper limit, the volatilization of lithium ions on the particle surface of the CAM can be reduced.

[0096] The firing temperature during the main firing is preferably 600 to 900° C., more preferably 650 to 850° C., and even more preferably 700 to 820° C. When the firing temperature is equal to or higher than the lower limit, a CAM having a strong crystal structure can be obtained. On the other hand, when the firing temperature is equal to or lower than the upper limit, the volatilization of lithium ions on the particle surface of the CAM can be reduced.

[0097] The firing temperature means the set temperature of the firing device. When the firing process is performed multiple times, the firing temperature means the temperature at the stage where the firing is performed at the highest temperature among the multiple firing stages. Examples of the firing device include a tunnel furnace, a continuous stationary firing furnace such as a roller hearth kiln, and a fluidized firing furnace such as a rotary kiln.

[0098] In the pre-baking and main baking, the retention time is preferably 1 to 50 hours, more preferably 2 to 20 hours. When the retention time in baking is equal to or less than the upper limit of the range, the volatilization of lithium ions is suppressed, and the deterioration of battery performance is suppressed. When the retention time in baking is equal to or more than the lower limit of the range, the development of crystals is inhibited, and the deterioration of battery performance is suppressed.

[0099] The fired product may be washed, dried, and crushed, if necessary.

[0100] [Addition process] A compound containing element M is added to the obtained fired product. Examples of compounds containing element M include metal salts containing element M, such as sulfates, hydroxides, carbonates, acetates, or nitrates containing element M. Examples of compounds containing element M include Ca(OH)2, CaSO4, CaCO3, (CH3COO)2Ca, Ca(NO3)2, Al(OH)3, Al2(SO4)3, Al2(CO3)3, Al(NO3)3, and Al(CH3COO)3.

[0101] The metal salt containing element M is preferably added in an amount such that the element M is more than 0 mol % and 3 mol % or less relative to the total amount of elements other than Li and oxygen atoms (for example, Ni, M1, M2) contained in the fired product. By setting the amount of the metal salt containing element M to the above range, it is possible to produce a CAM that satisfies the above condition (2) and preferably has an oxygen release rate and a filtrate pH in the above range, thereby improving the cycle characteristics of the lithium secondary battery.

[0102] During the above-mentioned addition step, water may be sprayed to promote the reaction. After the above-mentioned adding step, it is preferable to carry out a heat treatment. The temperature during the heat treatment is preferably 90 to 200° C. The heat treatment time is preferably 1 to 20 hours. Examples of the device used during the heat treatment include a vacuum drying device, a reduced pressure drying device, a blower, a heating device, and a combination of these devices.

[0103] After the heat treatment, the mixture may be crushed as appropriate. The CAM is obtained by the above steps.

[0104] In the above-mentioned CAM manufacturing method, the mixing step, the baking step, and the adding step are carried out in this order, whereby a CAM satisfying the above (1) and (2) can be manufactured. The CAM obtained by such a manufacturing method can improve the cycle characteristics of a lithium secondary battery.

[0105] <Lithium secondary battery> A positive electrode for a lithium secondary battery suitable for use with the CAM of this embodiment will be described below. Hereinafter, the positive electrode for a lithium secondary battery may be referred to as a positive electrode. Furthermore, a lithium secondary battery suitable for use as a positive electrode will be described.

[0106] An example of a suitable lithium secondary battery for use with the CAM of this embodiment has a positive electrode, a negative electrode, a separator sandwiched between the positive electrode and the negative electrode, and an electrolyte solution disposed between the positive electrode and the negative electrode.

[0107] 1 is a schematic diagram showing an example of a lithium secondary battery. For example, a cylindrical lithium secondary battery 10 is manufactured as follows.

[0108] First, as shown in the partially enlarged view of FIG. 1 , a pair of strip-shaped separators 1, a strip-shaped positive electrode 2 having a positive electrode lead 21 at one end, and a strip-shaped negative electrode 3 having a negative electrode lead 31 at one end are laminated in the order of separator 1, positive electrode 2, separator 1, and negative electrode 3, and then wound to form an electrode group 4.

[0109] The positive electrode 2, for example, has a positive electrode active material layer 2a containing CAM, and a positive electrode current collector 2b on one surface of which the positive electrode active material layer 2a is formed. Such a positive electrode 2 can be manufactured by first preparing a positive electrode mixture containing CAM, a conductive material, and a binder, and supporting the positive electrode mixture on one surface of the positive electrode current collector 2b to form the positive electrode active material layer 2a.

[0110] Examples of the negative electrode 3 include an electrode in which a negative electrode mixture containing a negative electrode active material (not shown) is supported on a negative electrode current collector, and an electrode made of only the negative electrode active material. The negative electrode 3 can be manufactured in a manner similar to that for the positive electrode 2.

[0111] Next, the electrode group 4 and an insulator (not shown) are housed in the battery can 5, the bottom of the can is sealed, the electrode group 4 is impregnated with an electrolyte solution 6, and the electrolyte is disposed between the positive electrode 2 and the negative electrode 3. Furthermore, the upper part of the battery can 5 is sealed with a top insulator 7 and a sealing body 8, whereby a lithium secondary battery 10 can be manufactured.

[0112] The shape of the electrode group 4 can be, for example, a columnar shape such that the cross-sectional shape when the electrode group 4 is cut perpendicular to the winding axis is a circle, an ellipse, a rectangle, or a rectangle with rounded corners.

[0113] The shape of a lithium secondary battery having such an electrode group 4 can be any shape defined by IEC60086, which is a standard for batteries defined by the International Electrotechnical Commission (IEC), or JIS C 8500. For example, cylindrical or rectangular shapes can be used.

[0114] Furthermore, the lithium secondary battery is not limited to the above-mentioned wound type configuration, and may be a laminated type configuration in which a laminated structure of a positive electrode, a separator, a negative electrode, and a separator is repeatedly stacked. Examples of the laminated type lithium secondary battery include a so-called coin type battery, a button type battery, and a paper type (or sheet type) battery.

[0115] For the positive electrode, separator, negative electrode, and electrolyte constituting the lithium secondary battery, for example, the configurations, materials, and manufacturing methods described in

[0113] to

[0140] of WO2022 / 113904A1 can be used.

[0116] <All-solid-state lithium secondary battery> The CAM of this embodiment can be used as a CAM for an all-solid-state lithium secondary battery.

[0117] Fig. 2 is a schematic diagram showing an example of an all-solid-state lithium secondary battery. The all-solid-state lithium secondary battery 1000 shown in Fig. 2 has a laminate 100 having a positive electrode 110, a negative electrode 120, and a solid electrolyte layer 130, and an exterior body 200 that houses the laminate 100. The all-solid-state lithium secondary battery 1000 may also have a bipolar structure in which a CAM and a negative electrode active material are arranged on both sides of a current collector. A specific example of the bipolar structure is the structure described in JP-A-2004-95400.

[0118] The positive electrode 110 has a positive electrode active material layer 111 and a positive electrode current collector 112. The positive electrode active material layer 111 contains the above-mentioned CAM and a solid electrolyte. The positive electrode active material layer 111 may also contain a conductive material and a binder.

[0119] The negative electrode 120 has a negative electrode active material layer 121 and a negative electrode current collector 122. The negative electrode active material layer 121 contains a negative electrode active material. The negative electrode active material layer 121 may also contain a solid electrolyte and a conductive material.

[0120] The laminate 100 may have an external terminal 113 connected to the positive electrode current collector 112 and an external terminal 123 connected to the negative electrode current collector 122. In addition, the all-solid-state lithium secondary battery 1000 may have a separator between the positive electrode 110 and the negative electrode 120.

[0121] The all-solid-state lithium secondary battery 1000 further includes an insulator (not shown) that insulates the laminate 100 from the exterior body 200 , and a sealing body (not shown) that seals the opening 200 a of the exterior body 200 .

[0122] A container molded from a highly corrosion-resistant metal material such as aluminum, stainless steel, or nickel-plated steel can be used as the exterior body 200. Also, a container formed into a bag shape from a laminate film having at least one surface treated to be corrosion-resistant can be used as the exterior body 200.

[0123] Examples of the shape of the all-solid-state lithium secondary battery 1000 include, for example, coin type, button type, paper type (or sheet type), cylindrical type, rectangular type, or laminate type (pouch type).

[0124] As an example, the all-solid-state lithium secondary battery 1000 is shown in a form having one laminate 100, but the present embodiment is not limited to this. The all-solid-state lithium secondary battery 1000 may have a configuration in which the laminate 100 is used as a unit cell and a plurality of unit cells (laminates 100) are sealed inside the exterior body 200.

[0125] Regarding the all-solid-state lithium secondary battery, for example, the configurations, materials, and manufacturing methods described in

[0151] to

[0181] of WO2022 / 113904A1 can be used.

[0126] Since the positive electrode having the above-described configuration has the CAM having the above-described configuration, the cycle characteristics of the lithium secondary battery can be improved.

[0127] Furthermore, since the lithium secondary battery having the above-described configuration has the above-described positive electrode, it has excellent cycle characteristics.

[0128] As described above, the preferred embodiments of the present invention have been described with reference to the accompanying drawings, but the present invention is not limited to such examples. The various shapes, combinations, etc. of the respective constituent members shown in the above examples are merely examples, and various modifications can be made based on design requirements and the like without departing from the gist of the present invention.

Example

[0129] Next, the present invention will be described in more detail with reference to examples.

[0130] <Composition analysis> The composition of the CAM was measured by the method of [Composition analysis] described above.

[0131] <Measurement of X and Y> X and Y of the CAM were measured as described in the above [Measurement method of X and Y].

[0132] <Measurement of Q and R> The Q and R of the CAM were measured as described in the above [Method for Measuring Q and R].

[0133] From the obtained X, Y, Q, and R, “(Q / X)×100” and “(R / Y)×100” were calculated.

[0134] <Measurement of BET Specific Surface Area> The BET specific surface area was measured by the method of the above [BET Specific Surface Area].

[0135] <Measurement of pH of Filtrate> For the filtrate obtained according to the description of the above [Method for Measuring Q and R], the pH at a liquid temperature of 25 °C was measured.

[0136] The presence or absence of Ba in the pores of the secondary particles of the CAM was carried out as described in [Method for Confirming Ba in Cross-Section of Secondary Particles].

[0137] <Measurement of Oxygen Release Rate> The oxygen release rate was measured as described in the above [Method for Measuring Oxygen Release Rate].

[0138] <Method for Measuring Cycle Retention Rate> The cycle retention rate of the lithium secondary battery was measured by fabricating the lithium secondary battery according to the above [Method for Measuring Cycle Retention Rate].

[0139] <Example 1> After putting water into a reaction tank equipped with a stirrer and an overflow pipe, an aqueous sodium hydroxide solution was added, and the temperature of the reaction tank was maintained at 70 °C. An aqueous nickel sulfate solution, an aqueous manganese sulfate solution, and an aqueous aluminum sulfate solution were mixed at a ratio such that the molar ratio of Ni, Mn, and Al was 93:1:6 to prepare a mixed raw material solution. Next, in the reaction vessel, an aqueous solution of ammonium sulfate was continuously added as a complexing agent to the mixed raw material liquid under stirring. An aqueous solution of sodium hydroxide was added dropwise at appropriate times so that the pH of the mixed liquid in the reaction vessel became 10.7 (measured at a liquid temperature of 40°C), and a reaction precipitate was obtained. After washing the reaction precipitate, it was dehydrated in a centrifuge and dried at 105°C for 20 hours to obtain a metal composite hydroxide. The metal composite hydroxide was oxidized in air at 650°C for 5 hours to obtain the metal composite oxide MCC-1.

[0140] MCC-1 and lithium hydroxide monohydrate powder were weighed out in a molar ratio of Li / (Ni+Mn+Al)=1.03. Barium hydroxide was weighed out in a ratio where the amount of Ba relative to the total amount of Ni, Mn and Al contained in MCC-1 was 0.5 mol%. MCC-1, lithium hydroxide monohydrate and barium hydroxide were mixed to obtain mixture 1. The obtained mixture 1 was pre-fired at 650°C for 5 hours in an oxygen atmosphere. It was further fired at 750°C for 5 hours in an oxygen atmosphere to obtain fired product 1. Next, calcium sulfate was weighed out in a ratio where the amount of Ca relative to the total amount of Ni, Mn and Al contained in fired product 1 was 1.0 mol%. Calcium sulfate was added to fired product 1 while spraying water, and then vacuum dried at 120°C for 10 hours to obtain CAM-1. In the above formula (I), CAM-1 had a = 1.03, b = 0.01, c = 0.005, d = 0.07, M1 = Mn, and M2 = Ca and Al. As shown in Figure 3, Ba was present in the pores of the secondary particles of CAM-1.

[0141] <Example 2> Aluminum sulfate was weighed out so that the amount of Al was 1.0 mol% relative to the total amount of Ni, Mn, and Al contained in the above-mentioned fired product 1. Aluminum sulfate was added to the fired product 1 while spraying water, and then the mixture was vacuum dried at 120°C for 10 hours to obtain CAM-2. In the above formula (I), CAM-2 had a=1.03, b=0.01, c=0.005, d=0.07, M1=Mn, and M2=Al. In CAM-2, Ba was present in the pores of the secondary particles.

[0142] <Comparative Example 1> The above MCC-1 and lithium hydroxide monohydrate powder were weighed out in a molar ratio of Li / (Ni+Mn+Al)=1.03. MCC-1 and lithium hydroxide monohydrate were mixed to obtain mixture 3. CAM-3 was obtained in the same manner as in Example 1, except that mixture 3 was used. In CAM-3, in the above formula (I), a=1.03, b=0.01, c=0, d=0.06, M1=Mn, and M2=Al.

[0143] <Comparative Example 2> The above-mentioned fired product 1 was directly used as CAM-4. In the above formula (I), CAM-4 had a = 1.03, b = 0.01, c = 0.005, d = 0.06, M1 = Mn, and M2 = Al. In CAM-4, Ba was present in the pores of the secondary particles.

[0144] <Comparative Example 3> The above MCC-1 and lithium hydroxide monohydrate powder were weighed out in a molar ratio of Li / (Ni+Mn+Al)=1.03. Barium hydroxide was weighed out in a ratio where the amount of Ba relative to the total amount of Ni, Mn, and Al contained in MCC-1 was 0.5 mol%. Calcium hydroxide was weighed out in a ratio where the amount of Ca relative to the total amount of Ni, Mn, and Al contained in MCC-1 was 0.5 mol%. MCC-1, lithium hydroxide monohydrate, barium hydroxide, and calcium hydroxide were mixed to obtain mixture 5. CAM-5 was obtained by carrying out the same procedure as in Example 1 except that mixture 5 was used. In CAM-5, in the above formula (I), a=1.03, b=0.01, c=0.005, d=0.07, M1=Mn, M2=Ca and Al. In CAM-5, Ba was present in the pores of the secondary particles.

[0145] <Comparative Example 4> The above MCC-1 and lithium hydroxide monohydrate powder were weighed out in a molar ratio of Li / (Ni+Mn+Al)=1.03. MCC-1 and lithium hydroxide monohydrate were mixed to obtain mixture 6. The obtained mixture 6 was pre-fired at 650°C for 5 hours in an oxygen atmosphere. It was further fired at 750°C for 5 hours in an oxygen atmosphere to obtain fired product 6. Next, barium nitrate and calcium sulfate were weighed out in a ratio such that the amount of Ba and Ca relative to the total amount of Ni, Mn, and Al contained in fired product 6 was 1.0 mol%. Barium nitrate and calcium sulfate were added to fired product 6 while spraying water, and then vacuum dried at 120°C for 10 hours to obtain CAM-6. In the above formula (I), CAM-6 had a=1.03, b=0.01, c=0.01, d=0.07, M1=Mn, M2=Ca and Al. In CAM-6, the presence of Ba in the pores of the secondary particles was not confirmed.

[0146] For Examples 1 and 2 and Comparative Examples 1 to 4, X, Y, Q, R, (Q / X)×100, (R / Y)×100, BET specific surface area, pH of the filtrate, oxygen release rate, and cycle retention rate are shown in Table 1.

[0147] [Table 1]

[0148] As shown in Table 1, in Examples 1 and 2 which satisfied the above (1) and (2), the cycle retention rates were both 87% or more, and it was confirmed that the cycle characteristics were excellent.

[0149] In Comparative Example 1, no compound containing Ba was added. The obtained CAM did not contain Ba and did not satisfy the above (2). Therefore, it is considered that side reactions tend to proceed when charging and discharging are repeated, resulting in poor cycle characteristics.

[0150] In Comparative Example 2, the addition step was not performed. In Comparative Example 3, a compound containing Ba was added in the mixing step, not in the addition step. The obtained CAM did not satisfy the above (2). This is thought to have resulted in poor cycle characteristics due to the side reaction occurring more easily on the surfaces of the secondary particles.

[0151] In Comparative Example 4, a compound containing Ba was added in the adding step, not in the mixing step. The obtained CAM did not satisfy the above (1). Therefore, it is considered that the reaction between lithium carbonate and hydrofluoric acid proceeded inside the secondary particles, and gas was generated, resulting in poor cycle characteristics. [Explanation of symbols]

[0152] 1: separator, 2: positive electrode, 2a: positive electrode active material layer, 2b: positive electrode current collector layer, 3: negative electrode, 4: electrode group, 5: battery can, 6: electrolyte, 7: top insulator, 8: sealing body, 10: lithium secondary battery, 21: positive electrode lead, 31: negative electrode lead, 100: laminate, 110: positive electrode, 111: positive electrode active material layer, 112: positive electrode current collector, 113: external terminal, 120: negative electrode, 121: negative electrode active material layer, 122: negative electrode current collector, 123: external terminal, 130: solid electrolyte layer, 200: exterior body, 200a: opening, 1000: all-solid-state lithium secondary battery

Claims

1. A positive electrode active material for a lithium secondary battery contains at least Li, Ba, and an element M, the element M being one or more elements selected from the group consisting of Ca and Al, and satisfies the following (1) and (2): (1) (Q / X)×100<0.1 (2) 1≦(R / Y)×100 (In (1) and (2), X is the amount of Ba (unit: ppm) contained in the positive electrode active material for lithium secondary batteries, measured by ICP emission spectroscopy; Y is the amount of element M (unit: ppm) contained in the positive electrode active material for lithium secondary batteries; Q is the amount of Ba (unit: ppm) contained in the filtrate, measured by ICP emission spectroscopy, obtained by filtering a suspension prepared by stirring the positive electrode active material for lithium secondary batteries and water in a mass ratio of 1:1; and R is the amount of element M (unit: ppm) contained in the filtrate.)

2. 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the filtrate has a pH of 12 or less when the liquid temperature is 25°C.

3. BET specific surface area is 2.0m 2 The positive electrode active material for a lithium secondary battery according to claim 1 or 2, wherein the Mo content is 1 / g or less.

4. The positive electrode active material for a lithium secondary battery according to claim 1 or 2, which satisfies the following formula (I): Li:Ni:M1:Ba:M2=a:(1-b-c-d):b:c:d...Formula (I) (M1 is one or more elements selected from the group consisting of Co and Mn, M2 is one or more elements selected from the group consisting of Al, Ca, Fe, Cu, Ti, Mg, Zn, Sn, Zr, Ga, W, Mo, Nb, B, Si, S, and P, and formula (I) satisfies 0.9≦a≦1.2, 0≦b≦0.2, 0<c≦0.03, and 0<d≦0.2.)

5. 3. The positive electrode active material for a lithium secondary battery according to claim 1, comprising secondary particles which are aggregates of primary particles, the secondary particles having pores, and Ba being present in the pores in a cross-sectional image of the secondary particles at a magnification of 5000 times obtained by a scanning electron microscope.

6. 3. The positive electrode active material for lithium secondary batteries according to claim 1, wherein a lithium secondary battery produced using the positive electrode active material for lithium secondary batteries is fully charged at 4.3 V, and then a positive electrode active material layer contained in the charged lithium secondary battery is subjected to simultaneous differential thermal and thermogravimetric analysis to obtain a maximum oxygen release rate of 1.5% / min or less.

7. A positive electrode for a lithium secondary battery, comprising the positive electrode active material for a lithium secondary battery according to claim 1 or 2.

8. A lithium secondary battery comprising the positive electrode for lithium secondary batteries according to claim 7.

9. A method for producing a positive electrode active material for a lithium secondary battery, comprising: a mixing step of mixing a metal composite compound, a lithium compound, and a compound containing Ba to obtain a mixture; a firing step of firing the mixture to obtain a fired product; and an adding step of adding a compound containing element M to the fired product, wherein the element M is one or more elements selected from the group consisting of Ca and Al.

Citation Information

Patent Citations

  • Positive electrode active material for nonaqueous electrolyte secondary batteries, and nonaqueous electrolyte secondary battery

    WO2021152997A1